Integration of Villages into WUAs: The Rising Challenge for Local Water Management in Uzbekistan - Mukhamedova, Nozilakhon; Wegerich, Kai (International Journal of Water Governance, 2014)
Although originally conceived as farmer organizations, today water user associations (WUAs) are expected to incorporate different water users and uses. However, the inclusion of different client groups in WUAs’ governance and management structure and the expansion of their service provision appear to present certain challenges. Using a case study from Uzbekistan, this paper explores whether a recently established WUA is able to integrate small users in village settlements and to provide services to meet the rising water demands of the rural population in Ferghana province. The finding shows that traditional water control, including technical, organizational, political and socio-economic components, is ill equipped to integrate the rural community. This challenge will increase with increasing population pressure and finite resources.